Observation of the inhomogeneous spatial distribution of MeV ions accelerated by the hydrodynamic ambipolar expansion of clusters. (December 2015) - Kanasaki, Masato; Jinno, Satoshi; Sakaki, Hironao; Faenov, Anatoly Ya.; Pikuz, Tatiana A.; Nishiuchi, Mamiko; Kiriyama, Hiromitsu; Kando, Masaki; Sugiyama, Akira; Kondo, Kiminori; Matsui, Ryutaro; Kishimoto, Yasuaki; et al.
Abstract: An inhomogeneous spatial distribution of laser accelerated carbon/oxygen ions produced via the hydrodynamic ambipolar expansion of CO2 clusters has been measured by using CR-39 detectors. An inhomogeneous etch pits spatial distribution has appeared on the etched CR-39 detector installed on the laser propagation direction, while homogeneous ones are appeared on those installed at 45° and 90° from the laser propagation direction. From the range of ions in CR-39 obtained by using the multi-step etching technique, the averaged energies of carbon/oxygen ions for all directions are determined as 0.78 ± 0.09 MeV/n. The number of ions in the laser propagation direction is about 1.5 times larger than those in other directions. The inhomogeneous etch pits spatial distribution in the laser propagation direction could originate from an ion beam collimation and modulation by the effect of electromagnetic structures created in the laser plasma. Highlights: A spatial distribution of ions due to hydrodynamic ambipolar expansion is measured. The homogeneous ion energy distribution of 0.78 ± 0.09 MeV/n is measured by CR-39. The number of ions in the laser axis is about 1.5 times larger than other directions.